Study on environmental behaviour of fluopyram in different banana planting soil - Jia Zhou (Nature Portfolio, 2021)
Abstract Fluopyram is commonly used to control banana leaf spot, anthracnose, and scab in tropical agricultural areas. To explore its behaviour in tropical agricultural environments, dissipation, adsorption, and leaching behaviours of fluopyram in three typical banana planting soils were studied. Also, its dissipation and migration capabilities in different regions and different soil types were evaluated. The results showed that the dissipation of fluopyram was in accordance with the first-order kinetic equation in the three banana soils, but the degradation rates were quite different. The degradation half-lives in the Hainan latosol, Yunnan sandy soil, and Fujian Plain alluvial soil were 46.21 days, 36.48 days and 57.76 days, respectively. Fluopyram also exhibited high adsorption and low leachability in the three soils. The Fujian Plain alluvial soil had the highest adsorption capacity for fluopyram, while fluopyram had the low leachability in the Yunnan sandy soil.